The Effect of The Strategies of Cognitive Harvesting And Writing Down Ideas on The Achievement of Geography Subject And The Development of Serious Thinking Among Students of The Fourth Grade (Journal of the College of Basic Education, 2025)
the research aims to identify (the effect of the strategies of cognitive harvesting and writing down ideas on the Achievement of geography subject and the development of serious thinking among students of the fourth grade). The research chose middle (the poet Muzaffar AL-Nawab) intentionally from the first Rusafa Education schools for the purpose of implementing the experimental there. The research sample consisted of (92) students in three classes , They were randomly distributed into three groups, The researcher equalize the three groups in many variables (prior knowledge , and the age ,and IQ , and previous geographical achievement, and prior serious thinking test). After the researcher determining the scientific material that included the fourth and fifth chapters of the book foundation of geography and lts techniques , he then analyzed the content of the two chapters of the material, for the purpose of determining its behavioral objectives which amounted to(120) goals according to all levels of Bloom classification, and in light of the objectives and content of the two chapters (22) teaching plans were prepared for each of the three groups . and two tests were used , the first is for Achievement including (40) test items, and the other for the serious thinking by the researcher which consisted of (25) items, and using one-way analysis and Scheffe test ,the researcher reached following results: (The students superiority of the first and second experimental groups on the students of the control in the achievement test) and (The students superiority of the first experimental group on the students of the control group in serious thinking posttest) .In the light of the above results, the researcher came conclusions and proposals, and recommended and recommendation for other studies.